DEVELOPING ANIMATED DUBBING VIDEOS AS LEARNING MEDIA IN ENGLISH SPEAKING AT THE TENTH-GRADE STUDENTS OF SMA PANGUDI LUHUR - Andriani, Dwi; Afas, Muhammad Zainuddin; Lestari, Siti Lilik (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This study aims to develop a learning video in the form of animated dubbing videos and to determine the validity and feasibility of learning videos in building English-speaking skills in class X students at SMA Pangudi Luhur. The development method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and evaluation). After the animated video dubbing was developed, a validity test was carried out by 1 media expert and 1 material expert, and a practicality test was carried out by 1 educator to test the feasibility of using animated video dubbing. The results showed that animated video dubbing was valid and appropriate for use in learning, with the validity percentage of media experts at 88.25% (very valid) and material experts at 96.50% (very valid). The results of the data analysis using SPSS indicate that animated dubbed videos are effective in improving students' speaking abilities. This is demonstrated by a significant improvement between students' pre-test and post-test scores. Animated video dubbing can improve students' English-speaking skills. Students show interest and active participation in the use of animated video dubbing, as measured by student response questionnaires. The results of the student response questionnaire obtained a score of 65.80%, which showed students were interested and enthusiastic about the animated video dubbing used. Positive student responses to animated video dubbing indicate that this learning media can be an effective tool for enhancing narrative text learning in the classroom. Keywords : Animated dubbing videos, speaking, narrative text.